Optimizing the transition from the indoor to the beach season improves motor performance in elite beach handball players - Eils, E., Wirtz, S., Brodatzki, Y.; Zentgraf, K.; Büsch, D.; Szwajca, S. (German Journal of Exercise and Sport Research, 2022)
Beach handball athletes experience an overlap during their preparation phase for the beach and the indoor season for several weeks. This transition phase from playing on an indoor surface to a sand surface is crucial for players` performance levels both on the sand and indoor surfaces, but coaches and athletes alike are concerned about possible performance impairments when training on a sand surface while still playing indoors. Therefore, we aimed to evaluate the effects of a specific transition phase from the indoor to the beach season in elite beach handball athletes. With 29 elite athletes participating in the study, we evaluated their jumping (countermovement and drop jump) and sprinting (5-10-20m) performances and conducted a handball-specific agility test on both rigid and sand surfaces. In addition, we evaluated a drop long jump on a sand surface. Vertical jumping performance was analyzed using a 3D marker-based system on both rigid and sand surfaces under standardized laboratory conditions. All tests took place directly before and after a 6-week intervention program. The results showed that athletes in the intervention group significantly improved their performance in jumping (countermovement and drop long jump) compared to the control group. Furthermore, performance on a rigid surface was not only maintained for all tests but also significantly increased for the countermovement jump. Therefore, the intervention program is effective at improving performance during the transition from indoor to beach seasons without impairing indoor performance.